Propuesta para la implementación de Practicas Correctas de Higiene para la Asociación de Producción Agropecuaria Rancho las Marías - Bundschuh Valarezo, Barbara Lisbeth (2022)
The objective of this research is to develop a proposal for the Implementation of Correct Hygiene Practices (PCH) for the Rancho las Marías Agricultural Production Association, located on the shore of the Vía Aloag - Santo Domingo. This establishment has several drawbacks that are visible in terms of both the operational and production management. The administrator and other members of the association are unaware of certain procedures that are regulated by the National Agency for Sanitary Regulation, Control and Surveillance (ARCSA) and in which, due to the way this company is being carried out, they are not complying with them. This study was developed through verification tables and observation of the establishment, compiling the necessary information to adhere to the circumstances and needs of the company. The verification tables were applied directly to the establishment indicating: state of the internal and external infrastructure, utensils, materials and ingredients used for the entire process of making the products they offer, as well as ventilation, lighting, hygienic services; among others. Within the company, a high degree of non-compliance was evidenced within each evaluated parameter, thus reaching 51% of non-compliance at a general level, so the application of correct hygiene practices will strengthen the opportunities that the company has in this case. grow and be a benchmark at the national level, so the main purpose is to fully apply what is proposed in this research work.